Guidelines for Urological Surgeries in the COVID-19 Pandemic: Is it Time for Revision? - Ghahestani, Seyyed Mohammad; Kashi, Amir Hosein (Urology Journal, 2021)
In this correspondence the authors try to show that guidelines and recommendations including what was published by EAU rapid reaction group must be further updated and tailored according to different epidemiologic data in different countries. The authors assign the countries worldwide in three categories. First category comprises countries that experience the secondary surges smoother than the first one. The second category include countries with stronger or -merging and rising-secondary surges and the third category encompasses countries with successful initial response and secondary stronger but still more controllable surges. Authors proclaim that after passing the first baffling impact we find out that postponement strategies preached in many of these scout treatises are no more suitable at least for the countries delineated in the second category and can culminate in performance of procedures in worse. The authors proffer Iranian Urology Association COVID-19 Taskforce Pamphlet(IUA-CTP) as a paragonic document mentioning it’s the time we must recognise the wide variability of the situation in different regions and any advisory position must consider this huge variance in epidemiologic profile.